PERBANDINGAN POLITICAL BRANDING JOKO WIDODO DENGAN MA’RUF AMIN PADA PEMILU 2019 - , Syifa Safira; Eka Yulyana (Moderat : Jurnal Ilmiah Ilmu Pemerintahan, 2024)
Political branding is part of broader political marketing. Political branding is a way for politicians or political parties to build a public image of themselves to influence voters, gain political support and win elections. The urgency of the main problem in comparing the political branding of the two includes the combination of their contrasting characters and backgrounds, Jokowi is known as a popular and modern leader, while Ma'ruf Amin brings a religious and conservative image, this pair's attempt to overcome social polarization by offering a balance between modernization and traditions, responses to external challenges, such as globalization and the digital economy, Jokowi is more proactive and Ma'ruf Amin is more focused on maintaining national values, the potential for synergy and conflict in their leadership, which can affect the stability and effectiveness of government, the role of the media and perceptions public that greatly influences political image and election results.